2013
DOI: 10.15835/nbha4118349
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Salinity on Seedling Growth of Some Pumpkin Varieties Used as Rootstock

Abstract: In this study, the effects of different salinity levels (0, "control", 2, 4, 8, and 12 dS m -1 ) on seedling growth of Obez, RS 841 and Ferro F 1 pumpkin varieties, widely used around the world as rootstock, were investigated. Seedlings grown under saline conditions were investigated for plant main stem length, plant length, root length, shoot length, root fresh weight, root dry weight, shoot fresh weight, shoot dry weights and ion concentrations (Ca ++ , K + , Na + ) in the leaves of pumpkin varieties. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
4
11
1
2
Order By: Relevance
“…The obtained results from the present study is similar to studies on different plants such as potato (Heuer and Nadler, 1995); tomato (Lopez and Satti, 1996); pumpkin (Kurum et al, 2013); R. sativus L. (Jamil et al, 2007).…”
Section: Effect Of Nacl and Ha On Growth Parameters And Of Mung Bean supporting
confidence: 89%
See 4 more Smart Citations
“…The obtained results from the present study is similar to studies on different plants such as potato (Heuer and Nadler, 1995); tomato (Lopez and Satti, 1996); pumpkin (Kurum et al, 2013); R. sativus L. (Jamil et al, 2007).…”
Section: Effect Of Nacl and Ha On Growth Parameters And Of Mung Bean supporting
confidence: 89%
“…However, the root fresh weight decreased (57%) significantly (P=0.018) in S2 compared to controls. A decrease in root fresh weights have been recorded in various plants grown under salinity such as wheat and barley (Adiyaman, 2005); tomato (Lopez and Satti, 1996); Pumpkin (Kurum et al, 2013). The present study revealed that for mung bean seedlings grown with salt and HA together (S1HA and S2HA), RFW increased in both HA treatments, with a 40% and 43.4% increase in S1HA and S2HA, respectively, however, these differences were not significant.…”
Section: Effect Of Nacl and Ha On Growth Parameters And Of Mung Bean contrasting
confidence: 49%
See 3 more Smart Citations